Ectoparasite prevalence in Pashmina goats in Changthang: A pastoralnomadic area of Ladakh - SHABIR, MIR; YATOO, MOHD IQBAL; KANWAR, M S; KUBREVI, SYED SHAFAT; DAR, RUKSAR; ANGMO, KUNZES (The Indian Journal of Animal Sciences, 2018)
The present study was a part of the survey which was carried out on Pashmina goats during November 2014 to October 2015 from in and around Nyoma block of Leh in 13 villages. There were around 38,412 Pashmina goats in 228 flocks which were less than 8 years recorded from these areas. Young goats constituted around 15–20% of whole goat population. The male and female goat constituted about 27–32% and 68–73% of total adult population respectively. During the study, an attempt was also made to find out ectoparasite prevalence, which showed that 21.12% male, 32.89% female goats and 35.31% young ones were infested by single or mixed ectoparasites. The infestation rate of ectoparasites was significantly higher in females against male goats. The analysis also showed that the prevalence of ectoparasites was significantly higher in younger (35.31%) than adult goats (27.01%). The most common ectoparasites encountered were lice. Tick was present in very less predominance. Flea and mite were rarely present. The seasons of highest infestation of ectoparasites were autumn and winter (>65%), the least being spring and summer. Therefore, to reduce high prevalence of ectoparasites and their impacts on the productivity and health status in Pashmina goats, appropriate and strategic control measures by creating awareness among farmers through extension services is needed.